Professional management of Mosque finances at the Raodatul Jannah Mosque in Laikang Village - Amran Amran; Nugroho Dwi Prihandoko; Arfandi Arfandi; Nurhani Nurhani; Chairul Ikhsan; Syamsuddin Syamsuddin; Muhammad Nur Abdi; Muh Nasrun; Muhaimin Muhaimin (Central Community Development Journal, 2023)
This study aims to explain the practice of financial management in mosques. The focus of this research is to explore and investigate how the financial management practices carried out by the Raodatul Jannah mosque in Laikang Village, Pangkajenne Regency. This research uses a case study method with several data collection techniques, namely interviews, observation, and document review. After the implementation of this Community Service, the knowledge/understanding of the Raodatul Jannah Mosque Management in Laikang Village in professional mosque financial management is getting better and can implement professionally related to the mosque's financial position report, mosque activity report, and mosque financial report. cash flow statement. So that the financial management of the Raodatul Jannah Mosque can obtain transparency and accountability.